Keberkesanan program latihan imageri terhadap tahap kebimbangan dan prestasi atlet memanah / Noni Maki - Noni , Maki (2018)

(untitled)
The sport of archery requires precision and focus of the utmost level. Factors such as pre-competition anxiety will reduce the level of concentration and focus of the athlete. Worry and anxiety causes the need for the athlete to adapt well in order to function optimally in situation that requires competitiveness (Urra, 2014). Study 1 was designed to assess the kind of pre-competition anxieties faced by athletes in archery and the type of mental skills they require. Study 2 and 3 are experimental studies to study the effect of imagery practice and physical practice on the performance of athletes in archery, to validate the effect of imagery practice on the aspects of cognitive anxiety, somatic anxiety and self-confidence of the athletes in a month, two weeks and a day before the competition. Subjects for Study 1 involved 38 athletes in archery from 12 secondary schools in Sabah, Study 2 involved 40 athletes in archery from University Malaysia Sabah while Study 3 involved 40 athletes in archery from the Sabah Archery Association. The instruments used were the Imagery Movement Application Questionnaire, Competitive State Anxiety Inventory-2R (CSAI-2R), Aiming Abilities by Grouping Performance Score Sheet, Social Validation Score Sheet and Mental Abilities Practice Suggestion Sheet. For the Intervention Program, the subjects were divided into two groups, namely the imagery group and the control group. The imagery group performed a combination of physical and imagery practices while the control group only performed physical practices. Improvements were made in Study 3 with regards to the distance of shooting and the intervention program. The findings of Study 1 showed that archery athletes experienced pre-competition anxiety and needed imagery and concentration practices, self-talk and positive attitudes in the psychological practice. Study 2 showed that the post research score for the imagery group to be significantly different in the aspect of performance of focused aiming skills (t= -7.197, df=8.5, p<.05.) compared to the control group (t= -3.833, df=19, p<.05.). Furthermore, the imagery group also showed a significant difference in the visual aspect (t=-6.957, df=19, p<.05.) and kinesthetic aspect (t= -7.341, df=19, p<.05.) compared to the visual aspect (t= -2.042, df=19, p<.05.) and kinesthetic aspect (t= -2.372, df=19, p<.05.) of the control group. The imagery group also had anxiety level for a month, two weeks and a day before the competition based on the cognitive aspect (M=66.0, SD=9.6; M=42.2, SD=6.0; M=34.8, SD=4.9), somatic aspect (M=65.9, SD=10.9; M=65.4, SD=10.8; M=56.0, SD=8.0) and self-confidence aspect (M=42.5, SD=9.6; M=82.1, SD=11.6; M=88.3, SD=10.4) which was better than the control group. Study 3 showed that the post research score of the imagery group was more significant in the aspect of performance of focused aiming skills (t= -9.441, df=19, p<.05.) compared to the control group (t= -2.748, df=19, p<.05.). Furthermore the imagery group also showed a significant difference for the visual aspect (t=-9.365, df=19, p<.05.) and the kinesthetic aspect (t= -10.58, df=19, p<.05.) compared to the visual aspect (t= -1.710, df=19, p<.05.) and kinesthetic aspect (t= -1.371, df=19, p<.05.) of the control group. The imagery group also had anxiety level for a month, two weeks and a day before the competition based on the cognitive aspect (M=68.6, SD=10.2; M=53.3, SD=8.8; M=35.8, SD=5.7), somatic aspect (M=70.1, SD=10.9; M=55.9, SD=7.0; M=47.7, SD=5.6) and self confidence (M=39.4, SD=9.6; M=47.5, SD=6.3; M=72.3, SD=15.1) which was better than the control group. The overall findings of this research support the notion that the combination of imagery practice and physical practice help to improve the performance of athletes in archery with regards to aiming skills, increased the kinesthetic and visual imagery ability and also reduce the level of cognitive and somatic anxiety of athletes as well as heighten the level of self-confidence in them before competition. The research findings is helpful for coaches, trainers and sports activists to apply and help their athletes to reduce the level of anxiety and improve performance. They can practice imagery training and other techniques related to Psychological Skills Training.